Polarographic Analysis of Fatty Acids Obtained from the Seed of Persea americana - Vaidya, Neelam; Choure, Rakesh; Banerjee, A.K.; Pitre, K.S. (Asian Journal of Chemistry, 2010)
Persea americana is grown as an oil seed crop in Sikkim. The saponifiable portion of fixed oil from the seeds of the tree has been analyzed using polarographic technique, which has revealed the presence of saturated fatty acids with E1/2/Ep values equal to (1) -0.46/-0.48 V, (2) -0.56/-0.57 V, (3) -0.63/-0.69 V and (4) -0.80/-0.80 V versus SCE, corresponding to myristic acid (1.8 %), palmitic acid (10.9 %), stearic acid (0.85 %) and arachidic acid (0.56 %), respectively. Whereas the unsaturated acid mixture produced four waves/peaks with E1/2/Ep values equal to (1) -0.30/-0.32 V, (2) -0.48/-0.48 V, (3) -0.56/-0.567 V and (4) -0.64/-0.66 V versus SCE, indicating the presence of linoleic acid (10.2 %), oleic acid (70.6 %), gadoleic acid (0.67 %) and palmitoleic acid (4.37 %), respectively. The method has been successfully applied for the qualitative as well as quantitative analysis of fatty acids. Each of fatty acid present in the oil produced is well defined polarographic DCP and DPP signals in 0.1 M TMAB and 0.1 mM Cd2+ used as a supporting electrolyte as pH 4.0 ± 0.2.